2016
DOI: 10.1107/s2056989016016650
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis and crystal structure of a 1:2 co-crystal of 1,3,6,8-tetraazatricyclo[4.3.1.13,8]undecane (TATU) and 4-chloro-3,5-dimethylphenol

Abstract: In the crystal, the 1:2 co-crystalline adducts are linked by π–π stacking inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It has been indicated in the literature that cocrystallization by melting or mechanochemical processes may not be as efficient as solution methods due to the limited activity of the reactant molecules (Li et al, 2018), but it has also been reported that an increased mixing intensity could contribute to improved cocrystal yield (Dhumal et al, 2010). Our previous work successfully demonstrated the feasibility of manufacturing cocrystals using mechanochemical processing (Rivera et al, 2015a(Rivera et al, , 2016a.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has been indicated in the literature that cocrystallization by melting or mechanochemical processes may not be as efficient as solution methods due to the limited activity of the reactant molecules (Li et al, 2018), but it has also been reported that an increased mixing intensity could contribute to improved cocrystal yield (Dhumal et al, 2010). Our previous work successfully demonstrated the feasibility of manufacturing cocrystals using mechanochemical processing (Rivera et al, 2015a(Rivera et al, , 2016a.…”
Section: Introductionmentioning
confidence: 80%
“…4-chlorophenol (Rivera et al, 2015a(Rivera et al, , 2016a, and the 2:1 adducts of TATD (3) with 4-bromophenol and 4-iodophenol (Rivera et al, 2015b(Rivera et al, , 2017b, crystal analysis shows that in (2a) and (3a), the 3-NP molecules are hydrogen bonded to N atoms of the same N-CH 2 -CH 2 -N moiety, which is the key structural parameter from the X-ray diffraction studies. However, although the molecular constitutions of compounds (2) and (3) differ only in the presence of one additional ethylene bridge in the tricyclic structure of (3), they nonetheless exhibit some marked differences in their conformations: in particular, the N-C-C-N torsion angles are À9.3 (5) (N1-C1-C2-N2) and 9.3 (4) (N3-C7-C8-N4) in cocrystal (3a), while the corresponding value of the N1-C2-C2-N1 torsion angle is 0.0 (2) , which indicates that the 42m symmetry of (3) is not maintained in the cage structure (Rivera et al, 2014;Murray-Rust, 1974).…”
Section: Figurementioning
confidence: 99%
“…The structure of the molecular aggregate was confirmed via melting point, 1 H NMR, 13 C NMR, and IR analysis. A single set of aliphatic and aromatic resonances can be assigned to the tricyclic tetraamine (TATU) and 4TBP molecules, respectively.…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%
“…Nowadays, the solid-state grinding, which is also known as mechanochemical synthesis, has developed as an interesting alternate method/technique for cocrystal synthesis [7][8][9][10]. We previously reported [11][12][13] that grinding a 1:1 mixture of 1,3,6,8-tetraazatricyclo[4.3.1.1 3,8 ]undecane (TATU, 1, Scheme 1) and different phenols (4-nitrophenol, 4-chlorophenol and 4-chloro-3,5-dimethylphenol) at room temperature for 15 min affords phenol-aminal 2/1 cocrystals in excellent yields, which have been assembled through hydrogen-bonding interactions. Furthermore, no side products are formed in the reaction mixture.…”
Section: Introductionmentioning
confidence: 99%